Multinationals Marketing Strategy in the Chinese Market - Krupka, Lukáš; Machková, Hana; Richter, Stanislav; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
The main goal of this master thesis is to identify the Chinese market and its consumer from the perspective of international and strategic marketing. China is one the most powerful and fastest growing market in the world belonging to the group of BRIC/BRIICS countries. As the economic development is growing, China has become an interesting market for many international and multinational companies where to spread their business activities. My aim is to analyze the main aspects of the Chinese market which directly influence the marketing strategy of the companies and understand the market's consumers' needs and preferences. A lot of international companies enter the Chinese market as they see a potential in 1,4 billion consumers living there. Chinese consumers are very specific. They become similar to the Western consumers as they have become richer but they still keep their traditional habits with their preferences. Unilever and P&G are examples of companies that succeeded in the Chinese market.
Vedoucí práce: Hana Machková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses